Analysis of Priority Criteria In Offering Special Mining Business Permit Areas (WIUPK) To Religious Community Organizations - Firlia Nurani Rakhma; Hanif Nur Widhiyanti; Tri Sulistiowarni (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2026)
This study examines the legal implications and urgency of setting priority criteria for the offering of Special Mining Business License Areas (WIUPK) to Religious Community Organization-Owned Enterprises (BU-OMK) as stipulated in Article 83A of Law Number 3 of 2020 and Article 75 of Government Regulation Number 96 of 2021. The main focus of the study lies in the lack of norms governing priority parameters, including aspects of feasibility, operational capacity, and verification mechanisms for BU-OMK. Using a normative juridical method based on analysis of laws and regulations and the principles of good mining governance, this study finds that this lack of regulation creates legal uncertainty and opens up broad scope for interpretation for decision-makers. As a result, there is potential for unequal treatment, conflicts of interest, and abuse of power in the process of granting WIUPK. This study also shows that giving priority to BU-OMK is a form of positive discriminatory policy (affirmative discrimination) that is theoretically justifiable, as long as it is implemented through a proportional, objective, and accountable mechanism. However, without clear priority criteria-including legality of the business entity, financial capability, technical capacity, environmental protection assurance, and governance integrity—this policy risks inefficiency and potential irregularities, including the use of BU-OMK as intermediaries for certain interests (beneficial ownership risks). Therefore, this study emphasizes the need for the establishment of comprehensive, auditable derivative regulations that align with the principles of government administrative law to ensure the effectiveness, accountability, and sustainability of the WIUPK bidding policy.